Matrix methods used in the risk analysis of water intakes - Szpak, Dawid; Boryczko, Krzysztof; Żywiec, Jakub; Rak, Janusz (Instal, 2021)
From 2017 risk assessment for water intakes is the basis for the decision to establish the indirect water protection zone. The work contains a review of the risk matrix methods, which are used in the risk analysis and assessment in the water supply system (WSS). Risk assessment was carried out for four surface water intakes, onshore type located in south-eastern Poland. Based on the results of the risk assessment, the need to establish new or adjust existing protection zones for analyzed water intakes was identified.
Keywords: risk analysis; water intake; water intake protection zone